DETERMINATION OF MALAYSIAN GOVERNMENT WEBSITE EVALUATION METRICS BASED ON THE ANALYTICAL HIERARCHY PROCESS - Mohd Helmi Rakhani; Hazura Mohamed; Ruzzakiah Jenal, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Telecommunications technology is constantly changing with more modern hardware, software and even networks, making it viable. Along with the sophistication, the government uses websites known as electronic government (E-Government) to deliver critical information, thus forcing the government to consider good website performance, compliance with the latest standards, user-friendly services, and digital services devices. In setting website evaluation criteria, the government lacks emphasis on the study of website evaluation metrics that can extend to website technology 5.0 and beyond. The website quality concept, consisting of various metrics and criteria, makes it difficult for stakeholders to analyse and set their priorities and importance in implementing web-based services. This study was carried out to develop the priority index of the metrics and criteria through the Analytical Hierarchy Process (AHP) method and confirm the priority of metrics and criteria based on comparing alternative positions obtained with the UN EGDI report for 2020 as a benchmark. The results of this study successfully classified five metrics out of 10 main metrics and 17 criteria out of 89 criteria metrics. The five main metrics for evaluating Government agency websites and their priorities identified in this study are Security, Performance, Content Structure, Technology and Accessibility. The discovery of these metrics and criteria gives exposure to all stakeholders in the website development process and its evaluation.